Pengembangan Sistem Informasi Pendaftaran Siswa Baru Berbasis Website Dengan Fitur Notifikasi Email di SMPN 11 Bulukumba - Dini Sri Astuti; Farida Farida; Iksan Rauf (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to: (1) Develop a Website-Based New Student Registration Information System with Email Notification Features at SMPN 11 Bulukumba, (2) Determine the results of the trial of the developed system, (3) Determine user responses to the developed system. This study uses the Research and Development (R&D) method with the 4D model (Four-D Models) which includes the Define, Design, Development, and Disseminate stages. The system was developed using the PHP, HTML, CSS, and JavaScript programming languages with MySQL as the database. System testing was carried out using the Black Box Testing method. The results of the study show that: (1) The system was successfully developed using the Unified Modeling Language (UML) which consists of use case diagrams, activity diagrams, sequence diagrams, and class diagrams. (2) The results of the system trial obtained a validity coefficient of 0.93 with a high validity category so that the system was declared suitable for use. (3) The results of user responses obtained from 31 respondents showed a percentage of 90% with a very good category.